KARAKTERISTIK PENYAKIT TUMOR BUAH PADA TANAMAN MERANTI MERAH (Shorea leprosula) DI KEBUN PANGKAS PT. SARI BUMI KUSUMA KECAMATAN SERAWAI KABUPATEN SINTANG - niyah, Isa; Diba, Farah; Darwati, Herlina (Universitas Tanjungpura, 2013)
The research aimed to know gall myte diseased characteristic on plant Shorea leprosula at pruning yard. of PT. Sari Bumi Kusuma at Serawai district, sintang regency. Research desaign used Completely Randomized Design (CRD) and sample plant is placed at random in observing slot and data analysis used Khi square ( Chi Square ) with 3 treatments and 6 replications. First plant normal or untrimmed (A0), second treatment is trimmed (A1) and third treatment is trimmed plan and given by vaseline at sectioned plant which is trimmed (A2). Total plant that is utilized were 18 plants. Result of the research showed that 33% plants S. leprosula was attack by gall myte, disease for all treatment. Result tests of Chi Square pointing out that the treatment given is not significant. Disease gall myte can be seen on branch tip part plant, leaf armpit and autotrof. Initially just as bruise with circumference gall myte + 1cm and long + 0,5cm and green chromatic. Time range of appearance gall myte until ranging break tumor were 93 115 days. Key word : gall myte, Shorea leprosula, pruning yard